Translating research into practice in low-resource settings: An Australian case study of early autism service provision in a regional town. Issue 1 (2nd January 2018) - Iacono, Teresa; Dissanayake, Cheryl; Hudry, Kristelle; Trembath, David; Erickson, Shane; Spong, Jo
ABSTRACT: Background We investigated the context for translating evidence-based early intervention for autism spectrum disorders (ASD) into real world settings through a case study of a regional town characterised as disadvantaged. Methods Data were from interview surveys of five managers reporting on 15 services, and surveys from 19 practitioners and 15 mothers of young children with ASD. Results The 15 services were multidisciplinary, offering diagnostic assessments ( n  = 2) and interventions delivered in the home and centres. Children were diagnosed at a mean age of 3 years; access to intervention was delayed and mostly limited to one session every two weeks. Some families travelled substantial distances to services, driving on average 50 minutes each way. Practitioners described intervention strategies in broad terms, rather than name interventions. Conclusions Services available to young children with ASD in this town were far removed from good practice in terms of early diagnosis, and intervention frequency and intensity.